Cigarette smoking augments androgen receptor activity and promotes resistance to antiandrogen therapy. Issue 10 (11th May 2019) - Shiota, Masaki; Ushijima, Miho; Imada, Kenjiro; Kashiwagi, Eiji; Takeuchi, Ario; Inokuchi, Junichi; Tatsugami, Katsunori; Kajioka, Shunichi; Eto, Masatoshi
Abstract: Background: Cigarette smoking is associated with worse outcomes in prostate cancer, whose growth is dependent on androgen receptor (AR) signaling. We aimed to elucidate the biological effect of cigarette smoking on AR signaling and its clinical influence on oncological outcome. Methods: Gene expression levels after exposure to tobacco smoke condensate (TSC) were evaluated by quantitative real‐time polymerase chain reaction and Western blot analysis in prostate cancer cells. Cellular sensitivities to enzalutamide and docetaxel after TSC exposure were evaluated using a prostate cancer cell proliferation assay. Prognosis was compared between current smokers and nonsmokers when treated with AR‐axis‐targeting (ARAT) agent enzalutamide and docetaxel. Results: Expression of AR variants as well as prostate‐specific antigen was augmented after TSC exposure, which occurred after Akt phosphorylation. These inductions were suppressed by Akt inhibitor LY294002 as well as antioxidant N‐acetylcysteine. Consistently, TSC exposure augmented cellular resistance to enzalutamide. In clinical data, cigarette smoking was associated with worse progression‐free survival and cancer‐specific survival when patients with prostate cancer were treated with ARAT agents but not docetaxel. Conclusions: It was suggested that cigarette smoking leads to detrimental oncological outcome when prostate cancer patients are treated with ARAT agents through induction of aberrant AR signaling. Accordingly, we recommend that patients with advanced prostate cancer should refrain from cigarette smoking.